Estudo representacional da participação familiar nas atividades dos centros de atenção psicossocial no município de Natal-RN - Azevedo, Dulcian Medeiros de (2008)
Comprehending social representations of users relatives of Psychosocial Care Centers (CAPS) from Natal-RN, about their participation in the activities of these services, was the purpose of this study. The research instrument used was a semi-structured interview, led to 28 relatives of users of East and West CAPS II, East and North CAPS-ad, involved in the Relative Therapeutic Group, in Relative Meeting, in the Assembly of Users, Technicians and Relatives, according to the therapeutic schedule of each health services, between August to November 2007. Data obtained in family and users identification were characterized with the aid of charts and boards in absolute and/or percentage values. The discursive material from the guide from interviews was submitted to the informational resource ALCESTE (Analyse Lexicale par Contexte d'un Ensemble of Segments of Texte), and analyzed on the basis of the Theory of Social Representations and Central Nucleus Theory. Most of the relatives were women, married, aged over 50 years, who participated for more than two years in CAPS activities, and a coexistence of more than 11 years with the user. From the classification system of ALCESTE were selected categories, identified by: Category 1, Treatment Improvements and Expectations; Category 2, Living User Before and After; Category 3, Activities Relevance, Contradictions and Suggestions; Category 4, Guidelines -- Psychopharmacology and Medicalization; Category 5, Family Participation and Activities; and Category 6, Therapeutic Conditions Thanks, Tips and Vulnerability. The social representation of the family exists in the desire for change, identifying that we need to promote change by the continuity of therapeutic activities and overcome the detected inconsistencies, targeted by strengthening and by the stability of improvements in living and health conditions of users, experienced in CAPS treatment. The central nucleus had corresponded to positive changes in health and living conditions of users, and the peripheral elements were constituted by family conducts before and during treatment, and the expectations of changes in activities, especially in workshops. Despite this family participation be considered important, it still does not meet conditions to promote the inclusion of family, under an emancipating point of view, capable of causing in subject the hope for autonomy, initiative, individual and collective growths, a closer and active involvement in therapeutic activities, in workshops and discussions